Gender equity and social inclusion in the Water-Energy-Food-Ecosystems (WEFE) nexus: Online learning module. - Jalonen, Riina; Zaremba, Haley; Petesch, Patti; Elias, Marlene; Estrada Carmona, Natalia; Tsvuura, Susan; Koirala, Sanju (2023)
This learning module shows how gender equity and social inclusion (GESI) considerations can be identified and integrated in programmes and initiatives in the Water-Energy-Food Environment (WEFE) Nexus. Intentionally focusing on gender and social inclusion in designing, implementing and monitoring Water-Energy-Food Environment initiatives is critical to ensure that these initiatives benefit and do not harm women and other marginalised groups and communities.